2018
DOI: 10.1111/tid.12982
|View full text |Cite
|
Sign up to set email alerts
|

Changes in practice and perception of hepatitis C and liver transplantation: Results of a national survey

Abstract: With new practice guidelines, it is important to understand how liver transplant (LT) centers have incorporated direct-acting antivirals (DAAs) into the management of hepatitis C virus-infected (HCV+) candidates and recipients. To explore how DAAs have affected LT centers’ willingness to treat HCV+ candidates and recipients and to use HCV+ donors, we surveyed high volume US LT centers (11/2014–12/2015) regarding practices for HCV+ candidates, recipients, and donors, before vs. after DAAs. We used the Scientifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
(80 reference statements)
0
10
0
Order By: Relevance
“…4,7,8 The aim of our study was to summarize the posttransplant outcomes after donor-derived HCV infection in non-viremic liver transplant recipients at our institution. 4,7,8 The aim of our study was to summarize the posttransplant outcomes after donor-derived HCV infection in non-viremic liver transplant recipients at our institution.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,7,8 The aim of our study was to summarize the posttransplant outcomes after donor-derived HCV infection in non-viremic liver transplant recipients at our institution. 4,7,8 The aim of our study was to summarize the posttransplant outcomes after donor-derived HCV infection in non-viremic liver transplant recipients at our institution.…”
Section: Introductionmentioning
confidence: 99%
“…4,7,8 The aim of our study was to summarize the posttransplant outcomes after donor-derived HCV infection in non-viremic liver transplant recipients at our institution. 1 In the context of this organ shortage, it is essential to make the best use of all transplantable organs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of HCV Ab+ donor organs for HCV Ab+ recipients has grown dramatically, particularly since curative interferon-free direct-acting antiviral (DAA) therapies became available. 1,[6][7][8][9][10][11][12][13][14] The risk of HCV transmission, which depends on the presence or absence of viremia, is an important consideration when using HCV Ab+ donors for HCV-recipients. 2,3 However, despite DAA availability and increased use among HCV Ab+ recipients, high-quality HCV Ab+ donor organs remain underutilized.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] In light of these factors and the persistent organ shortage, transplant centers have reported increasing willingness to use HCV Ab+ donors for HCV-uninfected (HCV-) recipients, and there is some evidence that this practice is growing. 1,[6][7][8][9][10][11][12][13][14] The risk of HCV transmission, which depends on the presence or absence of viremia, is an important consideration when using HCV Ab+ donors for HCV-recipients. 15 One study using 32 HCV Ab+ aviremic kidney donors for HCV-recipients found no subsequent HCV viremia among recipients, whereas another study using 26 HCV Ab+ aviremic liver donors for HCV-recipients found HCV transmission in four (16%) patients.…”
Section: Introductionmentioning
confidence: 99%